The architecture of smart city in Malaysia by utilizing IOTs - Ibrahim, Rosziati; Muhammed Asri, Noor Athirah; Jamel, Sapiee (2019)
Over the past few years, smart city components have been vastly discussed. Which components are considered necessary in order to build a smart city. This paper discusses the components that have been identified necessary in order to build the architecture for smart city in Malaysia. The architecture for smart city has been designed based on utilization of Internet of Things (IOTs).